2004
DOI: 10.1097/00005176-200402000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Histopathology, Iron Status and Iron Deficiency Anemia in Children with Helicobacter pylori Infection

Abstract: H. pylori infection was associated with a decrease in gastric juice ascorbic acid concentration, and this effect was more pronounced in patients with the CagA-positive strain. Pangastritis was more common in patients whose H. pylori.infection was accompanied by anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 30 publications
5
57
0
2
Order By: Relevance
“…Additional evidence was provided by five well-designed cross-sectional studies (16)(17)(18)(19)(20) , although two further studies failed to detect an association (53,54) . Four cross-sectional studies suggested that other indicators of low Fe status were associated with H. pylori (21)(22)(23)(24) , and five publications involving selected groups of subjects also supported a link between H. pylori and Fe-deficiency anaemia (25)(26)(27)(28)(29) . Conflicting results have been obtained from some communities.…”
Section: Discussionmentioning
confidence: 97%
“…Additional evidence was provided by five well-designed cross-sectional studies (16)(17)(18)(19)(20) , although two further studies failed to detect an association (53,54) . Four cross-sectional studies suggested that other indicators of low Fe status were associated with H. pylori (21)(22)(23)(24) , and five publications involving selected groups of subjects also supported a link between H. pylori and Fe-deficiency anaemia (25)(26)(27)(28)(29) . Conflicting results have been obtained from some communities.…”
Section: Discussionmentioning
confidence: 97%
“…Selenium, as in the form of selenocysteine, is involved in glutathione peroxidase, iodothyronine de-iodinase, and thioredoxin reductase enzymes [7]. Several studies have shown that H. pylori infection has relations to the deficiencies in copper, vitamin B12, folic acid, and vitamin A, C, and E [5,[8][9][10][11]. These deficiencies may be derived from anorexia caused by dyspeptic symptoms or from malabsorbtion secondary to intestinal bacterial infections, which is the result of hypo-achlorhydria in the stomach in the presence of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Once there, it is able to react with nitrosating agents preventing N-nitroso compounds formation; however, vitamin C in the stomach interacts with iron improving its absorption. In children, H. pylori infection was associated with reduced gastric juice ascorbic acid concentration, and the effect was more pronounced in patients with the CagA positive strain [20]. In adults, H. pylori infection is also recognized to lower the concentration of vitamin C in gastric juice as evident from a study involving randomly chosen 25-74 years old men and women of north Glasgow, UK.…”
Section: H Pylori and Vitamin Cmentioning
confidence: 99%
“…There is a single report suggesting the potential for H. pylori colonization of stomach of children without mucosal inflammation in antrum or gastric fundus [19]. Although, infection with the Cag Apositive strain was associated with more pronounced changes in the gastric physiology, limited studies in children reported no association between Cag A status and the severity of gastritis [20].…”
Section: Consequences Of Initial H Pylori Infection In Childrenmentioning
confidence: 99%
See 1 more Smart Citation